2020
DOI: 10.22625/2072-6732-2020-12-3-21-27
|View full text |Cite
|
Sign up to set email alerts
|

serum 25(oH)D level in patients with CoVID-19

Abstract: Recently, vitamin D deficiency is considered as a risk factor for the incidence and severity of new coronavirus infection. The aim of this work was to evaluate the vitamin D level of patients with COVID-19 hospitalized with communityacquired pneumonia and compare the value of 25(OH)D in blood serum with the clinical manifestations of the disease. Results. Included are 80 patients aged 18 to 94 years (mean age 53,2 ± 15,7 years), 43 (53,8%) men; with severe course – in 25 (31,3%) patients (12 males), and modera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…After their removal, no heterogeneity was found (Chi 2 P = 0.23, I 2 =27%), and the analysis still showed a statistical significance [MD −7.74 (−8.79, −6.69); p <0.00001]. Since in some studies the 25(OH)D levels were not measured in the same period as the cases [ 43 , 45 , 46 , 48 , 50 , 51 ], we excluded them from the analysis, but the statistical significance was maintained [MD −7.59 (−10.38, −4.81); p <0.00001] (Supplementary Fig. 1A) .…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…After their removal, no heterogeneity was found (Chi 2 P = 0.23, I 2 =27%), and the analysis still showed a statistical significance [MD −7.74 (−8.79, −6.69); p <0.00001]. Since in some studies the 25(OH)D levels were not measured in the same period as the cases [ 43 , 45 , 46 , 48 , 50 , 51 ], we excluded them from the analysis, but the statistical significance was maintained [MD −7.59 (−10.38, −4.81); p <0.00001] (Supplementary Fig. 1A) .…”
Section: Resultsmentioning
confidence: 96%
“…Finally, 29 articles met our inclusion criteria and, therefore, were included in this meta-analysis ( Fig. 1 ) [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] . Table 1 shows the main characteristics of the studies selected.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among 15 studies that assessed the relation between mortality and VDD, 13 studies were included in the analysis. Pooled analysis of 4 adjusted studies that used the Cox survival method ( 13 , 51 , 56 , 60 ) (HR: 2.35; 95% CI: 1.22, 4.52; I 2 : 84%; Figure 4 A ) and 5 studies ( 44 , 47 , 53 , 55 , 62 ) with crude OR (OR: 2.62; 95% CI: 1.13, 6.05; I 2 : 47.8%; Figure 4B ) indicated a significant association of VDD with mortality, while in adjusted studies that used logistic regression ( 54 , 59 , 65 ), no relation was observed (OR: 1.05; 95% CI: 0.63, 1.75; I 2 : 76.6%). Two studies were not included in the analysis since 1 study had an RCT design ( 36 ) and another one used different statistical methods ( 64 ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, 6 studies compared serum concentrations of 25(OH)D between deceased patients and those who survived ( 50 , 54 , 55 , 60 , 63 , 66 ); pooled analysis of studies indicated lower concentrations of 25(OH)D in patients who died compared with those who survived (WMD: −9.05 ng/mL; 95% CI: −13.86, −4.23; I 2 : 87.8%; Supplemental Figure 3 ). Results of studies are summarized in Supplemental Table 10 .…”
Section: Resultsmentioning
confidence: 99%